Health-Related Quality of Life in Patients With Locally Advanced Gastric Cancer Undergoing Perioperative or Postoperative Adjuvant S-1 Plus Oxaliplatin With D2 Gastrectomy: A Propensity Score-Matched Cohort Study - Yu, Jianhong; Wang, Zaozao; Li, Zhexuan; Liu, Ying; Fan, Yingcong; Di, Jiabo; Cui, Ming; Xing, Jiadi; Zhang, Chenghai; Yang, Hong; Yao, Zhendan; Zhang, Nan; et al. (Frontiers in Oncology, 2022)
Background: Some high-quality clinical trials have proven the efficacy and safety of perioperative and postoperative S-1 with oxaliplatin (peri-SOX and post-SOX) for patients with locally advanced gastric cancer (LAGC) undergoing D2 gastrectomy. However, little is known about how health-related quality of life (HRQOL) changes over time in patients receiving peri-SOX or post-SOX chemotherapy. Methods: A prospective observational cohort (NCT04408859) identified 151 eligible patients with LAGC who underwent D2 gastrectomy with at least six cycles of peri-SOX or post-SOX chemotherapy from 2018 to 2020. HRQOL was assessed using the EROTC QLQ-C30 and its gastric module, QLQ-STO22, at indicated measurements, including baseline and 1, 3, 6, and 12 months after initiation of therapy. Baseline characteristics, therapeutic effects, and longitudinal HRQOL were compared between the peri-SOX and post-SOX groups after propensity score matching. HRQOL changes over time and the risk factors for scales with severe deterioration were further analyzed. Results: No statistically significant differences in longitudinal HRQOL were observed between patients in the peri-SOX and post-SOX groups, with comparable surgical outcomes and adverse chemotherapy events. Scales of social functioning, abnormal taste, and anxiety improved earlier in the peri-SOX group than in the post-SOX group. Score changes in both groups indicated that general deterioration and slower recovery usually occurred in the scales of physical, social, and role functioning, as well as symptoms of fatigue, reflux, diarrhea, and anxiety. Conclusion: Peri-SOX showed a longitudinal HRQOL comparable to post-SOX in patients with LAGC who underwent D2 gastrectomy. The peri-SOX group had better performance in social functioning, abnormal taste, and anxiety at some measurements.